Răspuns :
a. (2a+3b)²= 4a²+12ab+9b²
b. (4x-y²)²= 16x²-8xy²+y^4
c. (x²-7y)²= x^4-14x²y+49y²
d. (4x²+x)²= 16x^4+8x³+x²
e. (7-3x²)² = 49-42x²+9x^4
f. (4x³-1)²= 14x^6-8x³+1
g. (3x²-1)² = 9x^4-6x²+1
h. (x²+2)² = x^4+4x²+4
i. (3x-√3)²= 9x²-6x√3+3
j. (2x-√5)²= 4x²-4x√5+5
k. (3x-2√3)²= 9x²-12x√3+12
l. (√2x-3)²= 4x²-6x√2+9
m. ( √3x +2)² = 3x²+4x√3+4
n. (3a-√2)² = 9a²-6a√2+2
(√2+√5)²= 4+2√10+5
(2a - 3√3)²=4a²-12a√3+27
(3a +2√2)²=9a²+12a√2+8
b. (4x-y²)²= 16x²-8xy²+y^4
c. (x²-7y)²= x^4-14x²y+49y²
d. (4x²+x)²= 16x^4+8x³+x²
e. (7-3x²)² = 49-42x²+9x^4
f. (4x³-1)²= 14x^6-8x³+1
g. (3x²-1)² = 9x^4-6x²+1
h. (x²+2)² = x^4+4x²+4
i. (3x-√3)²= 9x²-6x√3+3
j. (2x-√5)²= 4x²-4x√5+5
k. (3x-2√3)²= 9x²-12x√3+12
l. (√2x-3)²= 4x²-6x√2+9
m. ( √3x +2)² = 3x²+4x√3+4
n. (3a-√2)² = 9a²-6a√2+2
(√2+√5)²= 4+2√10+5
(2a - 3√3)²=4a²-12a√3+27
(3a +2√2)²=9a²+12a√2+8